Jackson-type inequalities and exact values of widths of classes of functions in the spaces S^p , 1 ≤ p < ∞ - Vakarchuk, S. B. (Ukrains’kyi Matematychnyi Zhurnal, 2004)
In the spaces S^p , 1 ≤ p < ∞, introduced by Stepanets, we obtain exact Jackson-type inequalities and compute the exact values of widths of classes of functions determined by averaged moduli of continuity of order m.